Criminal Liability of Perpetrators of Embezzlement in Office within a Limited Liability Company - Agus Wijaya, I Komang Jemi; M. Albarade Umaru Jaya; M. Sandy Firliano (Terekam Jejak Publisher, 2025)
Embezzlement in office is a criminal offense that frequently occurs in the corporate world, particularly within Limited Liability Companies (PT). This crime involves individuals within the company who abuse their position or the trust granted to them to unlawfully appropriate the company’s assets. Under Indonesian criminal law, embezzlement in office is regulated under Article 374 of the Criminal Code (KUHP). This journal aims to examine the forms of legal responsibility imposed on perpetrators of embezzlement in office within a PT, as well as the possibility of corporate criminal liability. The research method used is normative juridical, employing a statutory and case study approach. The results of the study indicate that perpetrators of embezzlement in office bear personal criminal liability; however, under certain conditions, the corporation itself may also be held criminally liable if the offense is committed on behalf of or for the benefit of the company.